Effects of hydrolysis conditions on recovery of antioxidants from methanolic extracts of Nigella Sativa seeds. - Tubesha, Zaki; Iqbal, Shahid; Ismail, Maznah (Academic Journals, 2011)
Nigella sativa (NS) has health promoting beneficial properties including antioxidant activity. In this study, the impact of acid and alkaline hydrolysis conditions on phenolic (TPC), flavonoid (TFC) contents and antioxidant activity of methanolic extracts from N. sativa (NS) seeds powder is evaluated. Total phenolic and flavonoid contents were evaluated according to Folin-Ciocalteu procedure and aluminium chloride colorimetric assays, respectively. The TPC extracts varied from 67 to 73 mg/100 g NS powder, expressed as Gallic acid equivalents (GAE), while TFC concentrations varied from 96 to 113 mg rutin equivalents (RE)/100 g NS powder. Positive correlations were found between TPC and TFC in NS hydrolyzates and their1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity (r2 = 0.975 and 0.978, respectively). The alkaline hydrolyzed extract (BHE) showed the highest TPC and TFC (730 µg GAE and1130 µg RE/g NS powder, respectively) as well as the highest antioxidant activity (DPPH• =167±0.133 mg TEAC /100 g dry NS, ABTS•+=112 ± 0.023 mg TEAC /100 g dry NS and FRAP=28 ± 0.159 mg GAE/100 g dry NS) compared to acid hydrolyzed (AHE) and non-hydrolyzed extracts (NHE). Non-hydrolyzed extracts showed the lowest TPC and TFC content (670 µg GAE and 960 µg RE/g NS powder, respectively) through the assays (p < 0.05). Findings of the study reveal that hydrolysis has profound effects on recovery of antioxidants from NS extracts. Overall, BHE has the highest antioxidant activity compared to AHE or NHE.